Accounting: business reporting for decision making - Birt, Jacqueline 1966 (Wiley Desktop Editions, 2008)
Accounting: Business Reporting for Decision Making, second edition is written for students who are required to complete a one-semester unit on introductory accounting. The text covers the basic principles of financial accounting, management and finance, as well as providing an introduction to ethics in business and corporate governance. It offers a broad, business-based introduction to the conceptual foundation of accounting and the use of accounting information for business decision making.